2018
DOI: 10.1093/jbcr/iry040
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Impact of Psychological Factors on Hospital Length of Stay for Burn Survivors: A Systematic Review

Abstract: Recovery of burn patients may be impeded by mental health problems. By gaining a better understanding of the impact that psychological factors may have on hospital length of stay, providers may be better informed to address the complex needs of burn survivors through effective and efficient practices. This systematic review summarizes existing data on the adverse psychological factors for the length of burn patients' hospitalization, and assesses the methodological quality of the extant literature on mental he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 32 publications
(84 reference statements)
0
11
0
1
Order By: Relevance
“…We found that longer hospitalization is independently associated with higher stress, anxiety, and depression. The association of psychological outcome with length of hospital stay has been described in numerous studies (23,24). However, this factor is not mentioned as a risk factor for psychological problems in COVID-19 survivors.…”
Section: Discussionmentioning
confidence: 99%
“…We found that longer hospitalization is independently associated with higher stress, anxiety, and depression. The association of psychological outcome with length of hospital stay has been described in numerous studies (23,24). However, this factor is not mentioned as a risk factor for psychological problems in COVID-19 survivors.…”
Section: Discussionmentioning
confidence: 99%
“…We realized the importance of psychosocial support for patients treated for burn victims to help them cope and adapt to burn injury [16][17]. A psychologist must be an integral part of the burn care team to help address psychological issues related to the burn trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, deep burn injury results in more conspicuous scars which are not only disfiguring but also functionally limiting and rehabilitation can be demanding and prolonged compared to superficial burns. We realized the importance of psychosocial support for patients treated for burn victims to help them cope and adapt to burn injury [ 16 - 17 ]. A psychologist must be an integral part of the burn care team to help address psychological issues related to the burn trauma.…”
Section: Discussionmentioning
confidence: 99%
“…In burn care, there is growing evidence of the adverse effect of mental health factors on burn injury [36]- [40], both in terms of incidence and recovery. Patients with pre-existing psychiatric illness may suffer more severe burn injuries, which occurs due to several reasons including confusion, carelessness, alcohol or drug intoxication or deliberate self-harm and attempted suicide [38].…”
Section: How Adverse Mental Health Could Impede Recoverymentioning
confidence: 99%